Pengaruh Body Massage Terhadap Skor Stres pada Ibu Postpartum - Lestari Sukma Abdiyanti; Ari Andayani (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2022)
Postpartum is a period after giving birth where a mother experiences both physical and psychological changes. These changes will have an impact on the mental health of the mother during the postpartum period. The results of a preliminary study at the TPMB Titin Sugiarti foundthat 7 of 8 mothers experiencing postpartum psychological disorder include anxietyand worry about not being able to take care of their baby properly, difficulty sleeping, severe fatigue while taking care of the baby, lack of time for yourself anddue to perineal scars. Non-pharmacologic efforts to help reduce anxiety and stress in postpartum mothers as an alternative option in providing interventions, namely body massage. The purpose of this study was to determine the effect of body massage on stress scores in postpartum mothers at TPMB Titin Sugiarti. This research is an experimental study with quantitative nature, using a quasi-experimental research design with pre and posttest without control with the number of respondents 20 postpartum mothers taken by consecutive sampling technique. The research instrument used a Perceive Stress Scale (PSS) questionnaire. Bivariate test using paired t test. The results showed that the average stress score before body massage was 17.00 and the average stress score after body massage was 13.20. The differencein the average stress score is 3,800 with a p value of < 0.05. Based on the bivariate test using a paired t test, p value = 0.000, it canbe concluded that Ha is accepted and Ho rejected, which means that there is an effect of body massage on stress scores in postpartum mothers at TPMB Titin Sugiarti. AbstrakPostpartum merupakan masa setelah melahirkan dimana seorang ibu mengalami perubahan baik fisik maupun psikologis. Perubahan-perubahan yang terjadi ini akan berdampak pada Kesehatan jiwa ibu pada masa nifas. Hasil studi pendahuluan di TPMB Titin Sugiarti didapatkan 7 dari 8 ibu mengalami gangguan psikologi postpartum dantaranya rasa cemas dan khawatir tidak dapat merawat bayinya dengan baik, kesulitan tidur, keletihan yangberat saat mengurus bayi, kurangnya waktu untuk diri sendiri dan rasa takut akibatbekas jahitan perineum. Upaya non pharmakologik untuk membantu menurunkan rasa cemas dan stres pada ibu postpartum sebagai pilihan alternatif dalam memberikan intervensi yaitu body massage. Tujuan penelitian ini untuk mengetahui pengaruh body massage terhadap skor stres pada ibu postpartum di TPMB Titin Sugiarti. Penelitian ini merupakan penelitian eksperimental yang bersifat kuantitatif, menggunakan quasi experiment dengan desain penelitian pre and posttest without control dengan jumlah responden 20 ibu postpartum yang diambil dengan teknik consecutive sampling. Instrumen penelitian menggunakan kuisioner Perceive Stress Scale (PSS). Uji bivariat menggunakan paired t test. Hasil penelitian menunjukkan rerata skor stres sebelum body massage adalah 17,00 dan rerata skor stres sesudah body massage adalah 13,20. Selisih rerata skor stres sebesar 3,800 dengan nilai p < 0.05.Berdasarkan uji bivariate menggunakan paired t test diperoleh nilai p=0,000 maka dapat disimpulkan Ha diterima dan Ho ditolak yang artinya terdapat pengaruh body massage terhadap skor stres pada ibu postpartum di TPMBTitin Sugiarti.